Symbolic Violence among Characters in Selected Eka Kurniawan’s Works - Christiana Anindya Putri (Indonesian Journal of English Language Studies (IJELS), 2020)
This article explores symbolic violence experienced by men and women in their everyday lives as portrayed in selected Eka Kurniawan’s works: Beauty is a Wound (2016), Man Tiger (2015), and Vengeance is Mine, All Others Pay Cash (2017). In order to identify the symbolic violence, Pierre Bourdieu’s concept of symbolic violence is applied in this research. The finding of this research indicates that symbolic violence experienced by men and women is the result of patriarchal system which is manifested in culture and tradition. This culture and tradition has power to discipline society and it also induces symbolic violence towards society since they are required to follow the patriarchal values or stereotype. The symbolic violence against men and women in selected Kurniawan’s works are depicted through arranged marriage, marital rape, women’s obligation in domestic domain, and men’s sexual performance and masculinity.